Bimbingan Konseling Spiritual Terhadap Pasien Rehabilitasi Napza - Ridho, Muhammad Hafizh (Jurnal Studia Insania, 2018)
This study aims to determine the spiritual behavior of patients rehabilitating drugs. This discussion is entitled "Spiritual Counseling Guidance to Rehabilitation Patients". This research is qualitative with a descriptive approach that is observation, an interview. The results showed that the implementation of the rehabilitation of the Patients of Drugs can also be in the form of personality by providing guidance and counseling on the spiritual aspect which includes the aspect of Prayer Fulfillment performed by the five subjects are conducted simultaneously namely the practice of worship, the belief of life (Universality) as well as the responsibility of their life (Linkage) they have fully undergone as rehabilitation patients. There are an attitude and mental change from a previously dependent patient to a person who can manage himself well and more appreciate the meaning of life.